EVALUATION OF MINERAL CONTENTS IN AFRICAN CATFISH SPECIES - Clarias gariepinus, Heterobranchus bidorsalis AND HYBRIDS OF BOTH SPECIES - OLANIYI, W.A (Nigerian Journal of Fisheries, 2015)
In this study, mineral contents of African catfish species of Clarias gariepinus, Heterobranchus bidorsalis and hybrids of both species were evaluated. Essential mineral elements such as available phosphorus, exchangeable cations (calcium, magnesium, potassium and sodium) and micronutrients (copper, zinc and iron) were determined. Data showed that the samples are excellent sources of all the minerals by providing optimal recommended dietary allowance except in calcium element. There were no significant differences (P > 0.05) in the mineral content of zinc (11.27 – 18.68 mg/kg), iron (50.5 – 105.76 mg/kg), calcium (0.33 – 0.49 Cmol/kg), phosphorus (10342.82 – 18956.80 mg/kg) and magnesium (2.35 – 2.89 mg/kg). Copper (mg/kg) varied significantly (P < 0.05) across the samples of C. gariepinus (2.92 ± 0.06), H. bidorsalis (1.48 ± 0.07), hybrid (1.69 ± 0.50) and reciprocal hybrid (1.36 ± 0.27). Manganese (mg/kg) indicated significant differences (P < 0.05) between C. gariepinus (3.19 ± 0.24) and H. bidorsalis (2.16 ± 0.22); while potassium (Cmol/kg) content of hybrid (33.65 ± 1.25) was significantly higher (P < 0.05) than that of H. bidorsalis (20.59 ± 0.01). Sodium levels (Cmol/kg) of C. gariepinus (17.53 ± 0.96) and reciprocal hybrid (27.58 ± 4.07) revealed significant difference (P < 0.05). These catfish products showed good composition of highly essential nutrients that promote nutrition security; therefore mineral contents should be the underlying determinant for quality products.